SISTEM INFORMASI UJIAN SEKOLAH ONLINE BERBASIS DATA WAREHOUSE (STUDY KASUS : SMP NEGERI 2 LURAGUNG) - Roni Sonjaya; aah sumiah; dadan nugraha (FKOM UNIKU, 2016)
Web based information system is in great demand in various circles, including in educational institutions, especially in institutions that have not been computerized, written test system that is often used in academic activities often have many obstacles. The cheating factor and the habit of cheating is the biggest obstacle, besides the factor of the slow assessment process in written test due to the many participants that can hamper the teacher in putting the value into the report card, waste paper and ink cost in making problem and doubling the problem including into negative factor in written exam, this study aims to create an online Data Warehouse based test system that can be utilized in educational institutions to change the current written exam into an online exam system. Therefore, in line with the rapid development of information technology, it is necessary to design and build an Online Data Warehouse based test system to replace the manual written test system. Where this system is expected to reduce the negative factors that often occur, as well as facilitate the teachers in SMP Negeri 2 Luragung in input data into the system, and can minimize operational costs in conducting exams in schools, as well as systems that will be made capable of storing data in large amounts and more secure in data storage, such as teacher data, principal data, student data, subject data, value data and data question.The method used is Data Warehouse, software development procedure using Waterfall method. The research respondents are the students of class IX in SMP Negeri 2 Luragung. Online test system is created by using PHP programming language, MySQL as database and XAMPP web server